2023
DOI: 10.1039/d2qi02416k
|View full text |Cite
|
Sign up to set email alerts
|

Solubilized LiNO3by the cationic size effect of CsF for lithium metal anode protection and dendrite formation prevention in carbonate electrolyte

Abstract: Lithium metal anodes attract researchers due to its high theoretical specific capacity and low redox potential. While the iterative side reactions of lithium and poor solubility of LiNO3 in routine...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…The XPS characterization of Li foil shows that the peaks in the F 1s, N 1s, and S 2p spectra at 685.0, 396.9, and 160.4 eV are corresponding to LiF, Li 3 N, and Li 2 S respectively (Figure S7). [31,32] These findings indicate that the Li foil surface primarily comprised inorganic species derived from the chemical reactions of FSI À anions with Li metal, which is also in line with Liu et al reported. [33] And the study demonstrated that the coulombic efficiency and cyclic performance of Cu/Li cells were promoted after Li metal was soaked in FSI À -anions electrolyte for several hours.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The XPS characterization of Li foil shows that the peaks in the F 1s, N 1s, and S 2p spectra at 685.0, 396.9, and 160.4 eV are corresponding to LiF, Li 3 N, and Li 2 S respectively (Figure S7). [31,32] These findings indicate that the Li foil surface primarily comprised inorganic species derived from the chemical reactions of FSI À anions with Li metal, which is also in line with Liu et al reported. [33] And the study demonstrated that the coulombic efficiency and cyclic performance of Cu/Li cells were promoted after Li metal was soaked in FSI À -anions electrolyte for several hours.…”
Section: Resultssupporting
confidence: 88%
“…To ascertain the self‐healing ability of V‐film, the chemical reactions of FSI − anions with Li metal was investigated after Li foil was soaked in a solution containing LiFSI and DME in a mass ratio of 1 : 2.32 (denoted as E1). The XPS characterization of Li foil shows that the peaks in the F 1s, N 1s, and S 2p spectra at 685.0, 396.9, and 160.4 eV are corresponding to LiF, Li 3 N, and Li 2 S respectively (Figure S7) [31,32] . These findings indicate that the Li foil surface primarily comprised inorganic species derived from the chemical reactions of FSI − anions with Li metal, which is also in line with Liu et al.…”
Section: Resultssupporting
confidence: 83%
“…Figure 10b-e show the capacity performance and EIS spectra of cells with LFP (areal capacity of cathode: 1.0 mAh cm −2 ) and NCA (areal capacity of cathode: 2.5 mAh cm −2 ) cathodes for lithium metal batteries containing CuF + LiNO3 in 1 M LiPF6 in EC/DEC (1:1 v/v), respectively. Additionally, it has been reported that the addition of CsF salts to conventional carbonate-based electrolytes increases the solubility of LiNO3 [100]. Because the Cs + ions in CsF salts have a minimum charge compared to the metal ion radius, the solubility of LiNO3 can be increased through cation size effects that lower the localization density of the charge.…”
Section: Carbonate-based Electrolytesmentioning
confidence: 99%
“…(g−j) Performance of Li||LFP cell using 1 M LiPF6 in EC/DEC (1:1 v/v) dissolved with 0.5 wt% CsF and 0.5 wt% LiNO3. (k) Visible solubility difference between electrolytes with dissolved pure LiNO3 and both CsF and LiNO3 in EC/DEC electrolyte [100]. Reprinted with permission from Ref.…”
Section: Carbonate-based Electrolytesmentioning
confidence: 99%
“…With the rapid development of new energy electric vehicles, aerospace, portable electronics, and other fields, [1][2][3][4] the traditional lithium-ion batteries with graphite as the anode cannot meet the needs of today's market because of their limited theoretical capacity (372 mA h g −1 ). [5][6][7] The search for anode materials with high specific capacity and energy density is the key to solving the current problem.…”
Section: Introductionmentioning
confidence: 99%